Bibliometric Study of the Innovation and Marketing of Services in the Restaurant Industry (2022)
The main objective of this research is to establish the most important advances and research related to the discipline of innovation and service marketing through scientific production within the restaurant industry through a bibliometric study of the literature in which related the incidence of the topics innovation and marketing of services within this particular industry. The methodology was a systematic review that focused particularly on the analysis of the literature where it was possible to include research carried out at in empirical and retrospective fields. These articles were extracted from the LENS.ORG database. It is concluded that it is essential to understand the processes related to innovation, transforming ideas into facts, and facts into market positioning. Innovating is being able to visualize all those situations in a way to do things faster, cheaper and easier; while the marketing study presented strategic frameworks in the continuous search for both the service offered and the satisfaction perceived by customers.  JEL Codes: C14, M31 Received: 17/05/2021.  Accepted: 14/09/2022.  Published: 01/0122022.